MODERN METHODS OF TEACHING MATHEMATICS - Adxamov Xasanboy Abdusalom òĝli; Abdurashitov Raxmatullo Abduxamitovich (American Journals, 2023)
The article discusses the possibilities and advantages of using interactive methods in mathematics lessons.
Keywords: school, education, interactive, teacher, pupil, spiritual-moral education, lesson, method.